Genome-wide identification, transcriptome analysis and alternative splicing events of Hsf family genes in maize - Zhang, Huaning (Sci Rep, 2020)
Heat shock transcription factor (Hsf) plays a transcriptional regulatory role in plants during heat stress and other abiotic stresses. 31 non-redundant ZmHsf genes from maize were identified and clustered in the reference genome sequenced by Single Molecule Real Time (SMRT). The amino acid length, chromosome location, and presence of functional domains and motifs of all ZmHsfs sequences were analyzed and determined. Phylogenetics and collinearity analyses reveal gene duplication events in Hsf family and collinearity blocks shared by maize, rice and sorghum. The results of RNA-Seq analysis of anthesis and post-anthesis periods in maize show different expression patterns of ZmHsf family members. Specially, ZmHsf26 of A2 subclass and ZmHsf23 of A6 subclass were distinctly up-regulated after heat shock (HS) at post-anthesis stage. Nanopore transcriptome sequencing of maize seedlings showed that alternative splicing (AS) events occur in ZmHsf04 and ZmHsf17 which belong to subclass A2 after heat shock. Through sequence alignment, semi-quantitative and quantitative RT-PCR, we found that intron retention events occur in response to heat shock, and newly splice isoforms, ZmHsf04-II and ZmHsf17-II, were transcribed. Both new isoforms contain several premature termination codons in their introns which may lead to early termination of translation. The ZmHsf04 expression was highly increased than that of ZmHsf17, and the up-regulation of ZmHsf04-I transcription level were significantly higher than that of ZmHsf04-II after HS.